Professional Advances in Sports Coaching : Research and Practice - Thelwell, Richard; Dicks, Matt; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Despite the rapid advance of the academic study of coaching science, there is a dearth of evidence on contemporary progressions within the coaching profession itself, particularly around the wide-ranging challenges that coaches face. Professional Advances in Sports Coaching constitutes an essential collection of the most innovative, up-to-date reviews and research on professional issues in sports coaching and coaching psychology.Seeking to assess and challenge contemporary conceptual and theoretical research around the evolving nature of the coach s role, issues associated with athlete and coach welfare, and societal demands of the coach, the book covers topics as diverse as:gender and spirituality within sports coaching;working in culturally diverse environments and disability sport;understanding hazing, mental health issues, and disordered eating in athletes;moral behaviour and safeguarding;high performance coaching and talent development;communicating with athletes in the age of social media, and managing cliques.Written by leading experts from around the world, every chapter clarifies and defines key concepts, gives an up-to-date and comprehensive review of literature within the area, and examines the implications for future research and applied practice. This is a critical resource for any upper-level student enrolled in sports coaching science or practice classes, sports coaching academics with an interest in professional practice, and practicing sports coaches.
1. The Professionalisation Of Sport CoachingJulian North, David Piggott, Sergio Lara-Bercial, Andrew Abraham, and Bob Muir2. The Theoretical Underpinnings of Transformational Coaching In Sport Jennifer Turnnidge and Jean Ct3.The Coaching Journey: Learning as Lifelong and Life-WideChristine Nash, Diane Culver, Koon-Teck Koh, Melissa Thompson, Larissa Galatti, and Tiago Duarte4. Working within Culturally Diverse Environments: The Role of Discourse in Identity Construction and the Implications for CoachingKerry R. McGannon, Jenny McMahon, and Chris Zenthner5. Sport for All: Considerations When Coaching in Disability Sport Understanding the Coaching LandscapeBecky Clark and Andrea Woodson-Smith 6. Exploring the Gender Divide in Current Day Sport Coaching Nicole M. LaVoi, Matea Wasend, and Anna Baeth7. Understanding and Supporting Spirituality in SportNoora J. Ronkainen8. Understanding the Coaches Role in Talent DevelopmentMelissa A. Chase, Emily Wright, and Justin S. DiSanti 9. Professional Issues and Ethics in Sport CoachingKristen Dieffenbach10. The Coachs Role on Moral Behaviour in SportMaria Kavussanu and Ken Hodge11. Safeguarding, Child Protection and Abuse: The Role of the Coach Daniel Rhind and Richard Blair12. Understanding Health-Compromising Behaviours in Athletes: Alcohol Use, Marijuana Use, Hazing, and Gambling Jennifer J. Waldron and Christopher L. Kowalski13. More Than Just A Coach: Developing Awareness Of Eating Disorders And Body Image Concerns In SportDana K. Voelker and Lindsey H. Schroeder14. The Coach as MentorSteven B. Rynne, Bob Crudgington, and Clifford J. Mallett15. Developing Mental Health Literacy in CoachesPaul Gorczynski16. Promoting and Protecting Coach Psychological Well-Being and PerformanceFaye F. Didymus, James L. Rumbold, and Helen R. Staff17. High Performance Sport Coaching: Leading Support Teams Toward Successful Performance Outcomes Jamie Youngson and Richard J. Keegan18. Managing Groups and Cliques Christopher R. D. Wagstaff, and Luc J. Martin19. Communicating with Athletes: The Influence of Social Media Stewart T. Cotterill20. Multilevel Model of Sport Injury (MMSI): Can Coaches Impact and be Impacted by Injury? Ross Wadey, Melissa Day, Francesca Cavallerio, and Laura Martinelli 21. Observing Coach Behaviours: Developing Coaching Practice And Coach Education?Chris Cushion22. Making Reflective Practice Beneficial Brendan Cropley, Andy Miles, and Zoe Knowles23. Knowing When, and How, To Step Out: Coach Retirement Claire-Marie Roberts, and Gran Kentt24. Think Aloud Protocol: Application to Athlete Cognition and Coach EducationAmy Whitehead.
Includes bibliographical references and index.
Also available in print format.
Keywords: SPORTS & RECREATION / Coaching / General; Coaching (Athletics) -- Research; Electronic books